Use of Neural Topic Models in conjunction with Word Embeddings to extract meaningful topics from short texts - HABBAT, Nassera; ANOUN, Houda; HASSOUNI, Larbi; NOURI, Hicham (EAI Endorsed Transactions on Internet of Things, 2022)
Unsupervised machine learning is utilized as a part of the process of topic modeling to discover dormant topics hidden within a large number of documents. The topic model can help with the comprehension, organization, and summarization of large amounts of text. Additionally, it can assist with the discovery of hidden topics that vary across different texts in a corpus. Traditional topic models like pLSA (probabilistic latent semantic analysis) and LDA suffer performance loss when applied to short-text analysis caused by the lack of word co-occurrence information in each short text. One technique being developed to solve this problem is pre-trained word embedding (PWE) with an external corpus used with topic models. These techniques are being developed to perform interpretable topic modeling on short texts. Deep neural networks (DNN) and deep generative models have recently advanced, allowing neural topic models (NTM) to achieve flexibility and efficiency in topic modeling. There have been few studies on neural-topic models with pre-trained word embedding for producing significant topics from short texts. An extensive study with five NTMs was accomplished to test the efficacy of additional PWE in generating comprehensible topics through experiments with different datasets in Arabic and French concerning Moroccan news published on Facebook pages. Several metrics, including topic coherence and topic diversity, are utilized in the process of evaluating the extracted topics. Our research shows that the topic coherence of short texts can be significantly improved using a word embedding with an external corpus.
Keywords: Neural Topic Models; Pre-training word embedding; Short text; Topic coherence